Optimal Super-Twisting SMC Design for CSTR via Improved Grey Wolf Optimization and Digital Implementation - Hammad Iqbal Sherazi (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The Continuous Stirred Tank Reactor (CSTR) is a widely studied system in the field of process control due to its nonlinear and time-varying behavior. Characterized by second-order nonlinear dynamics, it poses significant challenges in maintaining system stability and performance under varying operating conditions. Owing to these complexities, the CSTR is frequently employed as a benchmark model for evaluating the efficacy of modern control techniques. In this research, a condition-based Super-Twisting Sliding Mode Controller (STSMC) is developed to enhance the robust- ness and accuracy of the control system. The controller is specifically designed to handle the nonlinearities and external disturbances inherent to the CSTR process. A comprehensive stability analysis of the proposed control scheme is carried out using Lyapunov stability theory, ensuring that the system trajectories remain bounded and converge to the desired equilibrium. To further improve the control performance, the gains of the STSMC are optimally tuned using an Improved Grey Wolf Optimization (IGWO) algorithm. This metaheuristic optimization technique is employed to achieve faster convergence, better tracking performance, and reduced steady-state error. The complete control architecture is then implemented and validated on a Delfino C2000 digital controller to evaluate its real-time performance. Experimental results confirm the practical applicability and effectiveness of the proposed method in achieving stable and robust control of the CSTR system.